Reconsidering the value of covert research: the role of ambiguous consent in participant observation - Roulet, Thomas; Gill, Michael; Stenger, Sebastien; Gill, David James (Sage, 2017)
In this article, we provide a nuanced perspective on the benefits and costs of covert research. In particular, we illustrate the value of such an approach by focusing on covert participant observation. We posit that all observational studies sit along a continuum of consent, with few research projects being either fully overt or fully covert due to practical constraints and the ambiguous nature of consent itself. With reference to illustrative examples, we demonstrate that the study of deviant behaviors, secretive organizations and socially important topics is often only possible through substantially covert participant observation. To support further consideration of this method, we discuss different ethical perspectives and explore techniques to address the practical challenges of covert participant observation, including; gaining access, collecting data surreptitiously, reducing harm to participants, leaving the site of study and addressing ethical issues.